Designed to fail: evaluating grade 1-3 English first additional language textbooks as preparation for English medium grade 4 natural sciences and technology in South Africa - McAravey,GenéBarnard (School of Education, 2022)
Despite official school language policies mandating English as the medium of instruction from Grade 4 onwards, nearly half of South Africa's English Language Learners (ELLs) are obtaining less than 50% in their final (matric) English examinations. These same students are writing all of their other high school examinations in English. It seems clear that the majority of students do not have an adequate mastery of written English. What is the nature of the English language instruction these children are receiving? Especially in the earliest years of schooling? Are children being adequately prepared to learn through the medium of English? To investigate these issues, the research question for this study asked: 'Does children's learning of English in the subject English First Additional Language (EFAL) in Grades 1-3 prepare them to make sense of a Grade 4 Natural Sciences and Technology (NST) textbook?' This study employed content and discourse analysis, specifically relating to school textbooks and curriculum documents. The focus was on evaluating the readability of one Grade 4 NST textbook, in relation to the language resources provided by a Grade 1-3 English Language Teaching (ELT) scheme. The methodology employed was mixed methods, with elements of both quantitative and qualitative data analysis. Findings revealed that for all three key areas relating to text accessibility, namely Vocabulary, Genres and Syntax, the subject EFAL in Grades 1-3 does not adequately prepare learners to make sense of a Grade 4 NST textbook. Based on this, I recommend that learners no longer be made to transition to English as the Language of Learning and Teaching (LOLT) in Grade 4. Instead I recommend that children receive bilingual instruction throughout primary school in all learning areas, and that LTSMs and teacher training be updated to support this approach. I also recommend that EFAL and other home and additional languages be consolidated into a single language arts period and also taught bilingually. Alternatively, I recommend that learners be given two to three additional years to study EFAL before using it as a LOLT and that the EFAL course of study be revised to align more closely with the language and literacy demands of content subjects.